Pengabdian Budidaya Perikanan Masyarakat Pesisir Pada Desa Nyamplungsari, Kecamatan Petarukan, Kabupaten Pemalang, Provinsi Jawa Tengah - Agung Doni Anggoro; Sumiarsih Sumiarsih; Shinta Septiana; Ayu Rizki Amalia; Hermawan Gatot Priyadi; Muchtar Muchtar; Purwanto Purwanto; Dyah Retno Wulan; Marsono Marsono; Eddy Mustono; Wijatmika Wijatmika; Fatahuddin Fatahuddin; Tusana Nurul Safaah; Elmi Hidayah; Khaerudin HS (Community Service Journal (CSJ), 2024)
The aim of this community service activity is to increase the knowledge of fish farmers in Nyamplungsari Village, Petarukan District, Pemalang Regency regarding providing probiotics to milkfish nurseries in freshwater ponds. Training is carried out in three stages: preparation, implementation and evaluation. The material used during the training is making probiotics, distributing milkfish seeds, feeding and applying probiotics, measuring water quality, harvesting. After participating in the training activities, the training participants' knowledge increased, with an average pretest and post-test score of 50 to 90. Participants were very enthusiastic about receiving the material provided by the resource person. This activity went well and smoothly.